CONSUMPTION CULTURE IN THE PRESENCE OF GLOBALISATION: THE INFLUENCE OF RELIGION, NATION AND ETHNICITY ON CONSUMPTION PATTERNS - Ruževičius, Juozas; Ruževičiūtė, Rūta (Ekonomika, 2011)
The aim of this paper is to discuss existing consumption culture approaches and to analyse various consumption patterns determined by national, ethnic and religious differences. The current consumer culture is usually approached from two major positions: consumption homogeneity and consumption heterogeneity. Although globalisation has penetrated a number of areas in the modern world, one can see that consumption patterns have not become universal. The differences exist not just among the countries, but in some cases even within countries. The migration and population trends make these differences even higher. Even though the tendency of using the same products could be noticed all over the world, the reasons for consumption are different due to various national, religious or ethnical values. Paper type: general review.